The Effect of Profitability, Liquidity, and Company Size on Dividend Policy and Company Value (Case Study on Property and Real Estate Sector Companies listed on The Indonesia Stock Exchange for the 2015-2020 Period) - Oktaviana, Shanti Yesi Belina; Hapzi Ali; Rini Yayuk Priyati (Journal of Accounting and Finance Management, 2024)
For investors, a company’s value is reflected through share price performance. Meanwhile, the company’s financial performance and the company’s dividend decisions are considered to have an impact on the company’s value. This study aims to analyze the effect of profitability, liquidity, and company size on dividend policy and company value. The population used in this study is property and real estate companies listed on the Indonesia Stock Exchange in 2015-2020 with a sample of 78. The sample method used is purposive sampling using the Structural Equation Model-Partial Least Square (SEM-PLS) analysis approach. The conclusion of this study is that liquidity and company size positively affect dividend policy, while profitability doesn’t have a significant effect on dividend policy. Meanwhile, company size has a positive effect on company value, while liquidity has a negative effect on company value. Profitability and dividend policy don’t have a significant effect on the company’s value.